Hadoop mapreduce v2 cookbook : explore the hadoop mapreduce v2 ecosystem to gain insights from very large datasets - Gunarathne, Thilina (Community experience distilled., 2015)
If you are a Big Data enthusiast and wish to use Hadoop v2 to solve your problems, then this book is for you. This book is for Java programmers with little to moderate knowledge of Hadoop MapReduce. This is also a one-stop reference for developers and system admins who want to quickly get up to speed with using Hadoop v2. It would be helpful to have a basic knowledge of software development using Java and a basic working knowledge of Linux.